Prevalence of ABO and Rh Blood Groups and Their Association with Transfusion-Transmissible Infections (TTIs) among Blood Donors in Islamabad, Pakistan - Sijjeel, Farwa; Khalid, Ahmareen; Khan, Muhammad Yousaf; Khurshid, Rukhshan; Habiba, Umm E; Majid, Hina; Naeem, Mashal; Nawaz, Basharat; Nawaz, Basharat; Abbas, Safdar; Malik, Noor Ul Ain (BioScientific Review, 2021)
Certain Rh positive blood groups showed a link between the ABO blood grouping and susceptibility to some infectious ailments. Study was carried out to find the association of ABO Blood Group System / Rh type with different viral infection. A retrospective observational study was carried in 7631 blood donors to find the association of ABO Blood Group System / Rh type with viral infection due to hepatitis B virus, hepatitis C virus, human immunodeficiency virus and Syphilis. Data of the study indicateF that the highest incidence of blood group in blood donor was B followed by O, A and AB. The incidence of HBsAg +ve, HCV Ab +ve and infection of Syphilis was also highest in donor with blood group B followed by O, A and AB. Blood group A were more susceptible to HIV Ab +ve followed by blood group B, O and AB. The group B donors had the greatest risk of viral infection with HBV, HCV, HIV, and Syphilis; followed by the groups O, A, and AB. Donors in group AB had the lowest incidence rate of all viral infection. The study revealed that blood group B is most prevalent among donors, followed by blood groups O, A, and AB. On the other side, the rate of HBV, HCV, HIV, and Syphilis infection was greatest among group B donors, followed by group O, group A, and group AB. Keywords: ABO Blood Group System, hepatitis B virus (HBV), hepatitis C virus (HCV), human immunodeficiency virus (HIV), syphilis Copyright(c) The Authors